ANALYSIS ON THE POTENTIAL OF KERTA SEMAYA SAMINAYA TO ENTER THE GERMAN MARKET - Bhaskara, Ida Bagus Dwija; Purwanegara, Mustika Sufiati (Journal of Business and Management, 2018)
Abstract. Kerta Semaya Saminaya (KSS) is a sustainable Indonesian cocoa bean supplier. They produce organic fine or flavor cocoa beans that allows their product to become a premium. The problem however is that they are lacking buyers and wishes to expand their sales by exporting to a German buyer. This brings forth the question of if it is possible for KSS to enter Germany. To analyze and research this both qualitative and quantitative research methodology is used in this research to gain information and identify alternatives for improvement of actions. The primary data gathered is from interviewing German buyers, Indonesian supplier, survey German market segment and spreading questionnaires. For analysis technique, descriptive analysis is performed. To penetrate the German market, the only available option is to go through the niche market. To even sell to the German market a variety of requirements are needed ranging from basic to the niche requirements. One important requirement in Germany is sustainability which is also the aim of KSS. KSS has the capability to sell and compete in the German market however they still require certain certifications and conformity to be able to enter the market which could be overcome by selling through a wholesaler.Keywords: Cocoa bean, German market, niche cocoa market, Kerta Semaya Saminaya, sustainable, fine or flavor cocoa beans